Telenovela e receptor: dos meios às participações - Santos, Romilson Marco dos (2013)
The object of study is primetime soap operas and the transformations that define it, with the objective of establishing a relationship with the individual, the viewer. The study is conducted on the analysis of the soap operas narrative structure, their modifications, and finally, the consequences were established because of them. The beginning of this analysis, is the year 1964. We will therefore work, with a selection of daily soap operas such which have occurred since that date. The research problem focuses on the relationship established between changes in the narrative structure, its own visual soap opera language and the viewers' participation. Therefore we list the following assumptions: 1.Durring the soap operas actors do not interpret any character, but recreate the acts and circumstances occurring in everyday social life simulated by the plots, which allows us to affirm that the soap opera is life itself, and durring some time, the fictional game turns into life real.2. translation society by soap operas reaferms the traditional and conservative perception of Brazilian society. 3. the combination of mediation and its settings, where one comes to the generation of a visual language which constitutes the basis for the projection of social and drawings, as a consequence, to identify the way that society is allowed to see and / or be presented . The methodological basis of this research is based on the survey, selection, justification and comparative analysis of narrative structures and interference of the visability as a frame narrative structure itself. The most important area of this methodological strategy involves the comparison of the configuration processes and their communication trends in order to rescue a possible evolution of the enunciation of the outline of the Brazilian society. The theoretical basis is based on studies of Lucrece Ferrara, Roland Barthes, Mikhail Bakhtin, Charles Sanders Peirce: authors responsible for concepts such as interaction, analysis of narrative structure, author, character and semiosis